Swiss National Foundation SPARK Grant - Assis, Paulo de (SNSF, 2023)
Evaluation report and meeting for the Swiss National Foundation SPARK Grant.Spark enables researchers to test or develop novel and unconventional scientific approaches, methods, theories, standards and ideas within a short time. Preliminary data do not necessarily need to be available. Spark is aimed at researchers in all disciplines who have a doctorate or an equivalent qualification.
FRIS
1
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music